The Binding Effect of Constitutional Court Decisions on Police Regulations (An Analysis of Constitutional Court Decision No. 114/PUU-XXIII/2025) - Firmantoro, Kiki (IBLAM LAW REVIEW, 2026)
This study examines the binding force of Constitutional Court decisions on administrative regulations issued by the Indonesian National Police, with particular attention to the normative consistency between Police Regulation No. 10 of 2025 and the constitutional meaning articulated in Constitutional Court Decision No. 114/PUU-XXIII/2025. A normative legal research approach is employed through the analysis of constitutional norms, the hierarchy of laws and regulations, doctrines of constitutional and administrative law, and constitutional adjudication. The analysis demonstrates that Constitutional Court decisions possess substantive binding force, requiring the internalization of the ratio decidendi as a normative standard in the formulation of implementing regulations. Normative inconsistency between police regulations and constitutional standards risks generating vertical normative conflicts, undermining constitutional supremacy, and weakening the principles of the rule of law and constitutional democracy